2010
DOI: 10.1016/s0377-1237(10)80118-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Systemic Lupus Erythematosus Disease Activity Index, C3, C4 and Anti-dsDNA Antibodies

Abstract: Background: Therapeutic decisions in systemic lupus erythematosus (SLE) are based on the disease activity and nature of organ involvement. There are various clinical and laboratory methods to assess the lupus flares. Methods: Fifty one SLE patients with active disease (lupus flare) were studied. Systemic lupus erythematosus disease activity index (SLEDAI), C3, C4 and anti-double stranded DNA levels were estimated and repeated monthly till remission. After remission these tests were done three monthly. Values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 9 publications
4
25
0
Order By: Relevance
“…Other investigators have reported an association of plasma parameters, such as anti-dsDNA, C3 and C4, with disease activity. Our findings on plasma levels of anti-dsDNA, C3 and C4 and their correlation with the SLEDAI scores (Figure 2B, C and 2D) are in conformity to earlier reports [27,28]. The SLEDAI scores correlated positively with dsDNA antibody levels ( P = 0.002, r = 0.31), while it correlated negatively with C3 ( P < 0.0001, r = -0.39) and C4 (P = 0.0003, r = -0.40) respectively.…”
Section: Resultssupporting
confidence: 93%
“…Other investigators have reported an association of plasma parameters, such as anti-dsDNA, C3 and C4, with disease activity. Our findings on plasma levels of anti-dsDNA, C3 and C4 and their correlation with the SLEDAI scores (Figure 2B, C and 2D) are in conformity to earlier reports [27,28]. The SLEDAI scores correlated positively with dsDNA antibody levels ( P = 0.002, r = 0.31), while it correlated negatively with C3 ( P < 0.0001, r = -0.39) and C4 (P = 0.0003, r = -0.40) respectively.…”
Section: Resultssupporting
confidence: 93%
“…A study by Narayanan et al [29] have reported significantly high levels of anti-dsDNA, with lowest C3 and C4 levels in renal flare cases, as compared to non-renal flare cases. In addition, SLEDAI was positively correlated with anti-dsDNA and negatively correlated to C3 and C4 levels in renal flares, whereas no significant association was found among non-renal flare cases.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that more male patients in Jordan have LN than in other countries (neighboring and nonneighboring). This difference may be related to specific differences in pathogenesis among sexes, including genetic, hormonal, and immune-responses factors, in addition to racial and geographical variations in LN [18]. Further studies are warranted to establish the causes of the increased prevalence of LN among males in Jordan.…”
Section: Discussionmentioning
confidence: 99%